Factor 9y2 - 12y + 4

Question

Asked 3/9/2016 6:05:25 PM

Updated 3/10/2016 3:52:11 AM

2 Answers/Comments

This answer has been confirmed as correct and helpful.

f
freestar.config.enabled_slots.push({ placementName: 'weegy_incontent_1', slotId: 'weegy_incontent_1' });

(3y-2)^2

Batista|Points 397|

Question

Asked 3/9/2016 6:05:25 PM

Updated 3/10/2016 3:52:11 AM

2 Answers/Comments

This answer has been confirmed as correct and helpful.

Rating

8

1 - 2.25x^8

= 1 - (1.5x^4)^2

= (1 - 1.5x^4)(1 + 1.5x^4)

= 1 - (1.5x^4)^2

= (1 - 1.5x^4)(1 + 1.5x^4)

Added 3/10/2016 3:08:07 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/10/2016 3:51:58 AM]

8

x^2 - 9

= x^2 - 3^2

= (x - 3)(x + 3)

= x^2 - 3^2

= (x - 3)(x + 3)

Added 3/10/2016 3:09:01 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [3/10/2016 3:52:11 AM]

Perform the indicated operation.
(2u^2 - 7) ÷ (u + 3)

Question

Not Answered

Updated 4/20/2016 6:44:37 PM

1 Answer/Comment

(2u^2 - 7) ÷ (u + 3)

= (2u^2/u+3) - (7/u+3)

= 2u - 6 R. 11

= (2u^2/u+3) - (7/u+3)

= 2u - 6 R. 11

Added 4/20/2016 6:44:35 PM

This answer has been confirmed as correct and helpful.

Perform the long division (y^3 - 125) ÷ (y - 5) User: Multiply (6z^2 - 4z + 1)(8 - 3z) **Weegy:** (6z^2 - 4z + 1)(8 - 3z) = -18z^3 + 60z^2 - 35z + 8 **User:** Simplify b(a + b) - a(a - b). **Weegy:** b(a + b) - a(a - b) = ab + b^2 - (a^2 - ab) = ab + b^2 - a^2 + ab = 2ab + b^2 - a^2 (More)

Question

Updated 3/9/2016 11:05:33 PM

1 Answer/Comment

Simplify 5 + 2{x - 4[3x + 7(2 - x)]}. **Weegy:** 5 + 2{x - 4[3x + 7(2 - x)]} = (2x + 32x) + (5 - 112) = 34x - 107 **User:** Find the product.
(7q - 5)(7q + 5) **Weegy:** (7q - 5)(7q + 5) = 49q^2 + 35q - 35q - 25 = 49q^2 - 25 **User:** Find the quotient.
(35n^3 - 30n^2 + 25n) ÷ (-5n) **Weegy:** (35n^3 - 30n^2 + 25n) ÷ (-5n) = -7n^2 + 6n - 5 **User:** Find the product.
-2x(x^2 - 3) **User:** Find the product.
-mnp(3m - 5n + 7p) (More)

Question

Not Answered

Updated 3/9/2016 11:02:21 PM

2 Answers/Comments

-2x(x^2 - 3)

= -2x*x^2 + (-2x)*(-3)

= -2x^3 + 6x

= -2x*x^2 + (-2x)*(-3)

= -2x^3 + 6x

Added 3/9/2016 5:28:21 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [3/9/2016 11:02:45 PM]

39,050,467

questions answered

There are no comments.